Preclinical and clinical evidence for the treatment of non-alcoholic fatty liver disease with soybean: A systematic review and meta-analysis - Li, Yubing; Deng, Xinyu; Guo, Xiaochuan; Zhang, Fangling; Wu, Hefei; Qin, Xuhua; Ma, Xiao (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD), a prevalent public health issue, involves the accumulation of triglycerides in hepatocytes, which is generally considered to be an early lesion of liver fibrosis and cirrhosis. Thus, the development of treatments for NAFLD is urgently needed. This study explored the preclinical and clinical evidence of soybeans to alleviate NAFLD. Studies indexed in three relevant databases—Web of Science, PubMed, and Embase—between January 2002 and August 2022 were retrieved. A total of 13 preclinical studies and five RCTs that included 212 animals and 260 patients were included in the present analysis. The preclinical analysis showed that liver function indices (AST, SMD = −1.41, p < 0.0001 and ALT, SMD = −1.47, p < 0.0001) were significantly improved in the soybean group compared to the model group, and fatty liver indicators (TG, SMD = −0.78, p < 0.0001; TC, SMD = −1.38, p < 0.0001) and that oxidative stress indices (MDA, SMD = −1.09, p < 0.0001; SOD, SMD = 1.74, p = 0.022) were improved in the soybean group. However, the five RCTs were not entirely consistent with the preclinical results; however, the results confirmed the protective effect on the liver. The results of the clinical RCTs showed that soybean significantly affected liver function, fatty liver, and oxidative stress indicators (ALT, SMD = −0.42, p = 0.006; TG, SMD = −0.31, p = 0.039; MDA, SMD = −0.76, p = 0.007). The current meta-analysis combined preclinical and clinical studies and verified that soybean could protect the liver in NAFLD by regulating lipid metabolism and oxidative stress factors via the Akt/AMPK/PPARα signaling pathway. Soybean might be a promising therapeutic agent for treating non-alcoholic fatty liver disease. Systematic Review Registration: (https://www.crd.york.ac.uk/prospero/#myprospero), identifier (CRD42022335822).